Endogenous Inequality - Kiminori Matsuyama (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
Does the market economy exacerbate inequality across households? In a capitalistick society, does the rich maintain a high level of wealth at the expense of the poor? Or would an accumulation of the wealth by the rich eventually trickle down to the poor and pull the latter out of poverty? This paper presents a theoretical framework, in which one can address these questions in a systematic way. The model focuses on the role of credit market, which determines the joint evolution of the distribution of wealth and the interest rate. A complete characterization of the steady states is provided. Under some configurations of the parameter values, the model predicts an endogenous and permanent separation of the population into the rich and the poor, where the rich maintains a high level of wealth partially due to the presence of the poor. Under others, the model predicts the Kuznets curve, i.e., the wealth eventually trickles down from the rich to the poor, eliminating inequality in the long run.
Keywords: D31; O11; 330; Imperfect Credit Markets; Distribution of Wealth; Endogenous Inequality; Trickle-Down; The Kuznets Curve